Nanostructured Materials for the Detection of CBRN (Dordrecht : Springer Netherlands, 2018)
This book includes topics in nanophysics, nanotechnology, nanomaterials, sensors, biosensors, security systems, and CBRN agents detection. There have been many significant advances in the past two years and some entirely new directions of research are just opening up. Recent developments in nanotechnology and measurement techniques now allow experimental investigation of the physical properties of nanostructured materials. The book presents new methods for the detection of chemical, biological, radiological and nuclear (CBRN) agents using chemical and biochemical sensors. Identification, protection and decontamination are the main scientific and technological responses for the modern challenges of CBRN agents.
Part I Nanostructured Materials -- Chapter1: Strained Graphene Structures: From Valleytronics to Pressure Sensing -- Chapter2: Development of Biosensors Using Carbon Nanotubes and Few Layered Graphene -- Chapter3: Loaded Electrospun Nanofibers: Chemical and Biological Defense -- Chapter4: Graphene Quantum Dots, Graphene Non-circular n-p-n-Junctions: Quasi-relativistic Pseudo Wave and Potentials -- Chapter5: Magnetic Properties of nCoO/(1-n)ZnO Nanocomposites Obtained by Calcination -- Chapter6: Photocatalytic Properties of TiO2 Thin Films Doped With Noble Metals (Ag, Au, Pd and Pt) forWater Decontamination -- Chapter7: Electrical Measurements of the Dimensions of Nanostructures W. Nawrocki and Yu. M. Shukrinov -- Chapter8: Thermoelastic Phase Transformations and Microstructural Characterization of Shape Memory Alloys -- Chapter9: Nanostructured SnO2 as CBRN Safety Material -- Chapter10: New Experimental Approach to Measure the Photocatalytic Activity of the TiO2 Nanosample -- Chapter11: Boron-Containing Nanostructured Materials for Neutron-Shields -- Part II Nanosensors -- Chapter12: 12 Zeolite-Based Interfaces for CB Sensors -- Chapter14: Nanosensor Devices for CBRN-Agents Detection:Theory and Design -- Chapter14: Improving the Design of Ion Track-Based Biosensors -- Chapter15: Development of a Piezoelectric Flexural Plate-Wave (FPW) Biomems-Sensor for Rapid Point-of-Care Diagnostics -- Chapter16: Optical Polarization Characteristics of Zeolite Deposited on Different Substrates for Perspective Modulation Biosensor Systems -- Chapter17: Design, Analysis and Application of Dynamic Visual Cryptography for Visual Inspection of Biomedical Systems -- Chapter18: Information Processing in Chemical Sensing: Unified Evolution Coding by Stretched Exponential -- Chapter19: Toxicology of Heterocarbon and Application of Nanoheterocarbon Materials for CBRN Defense -- Chapter20: Carbon Nitride Oxide (G-C3N4)O and Heteroatomic N-Graphene (Azagraphene) as Perspective New Materials in CBRN Defense -- Chapter21: Polymer Nanocomposites with Silver Nanoparticles Formed by Low-Energy Ion Implantation: Slow Positron Beam Spectroscopy Studies -- Chapter22: Heterogeneous Systems with Ag Nanoparticles -- Chapter23: CBRN Risk Scenarios -- Chapter24: Influence on the Energy Efficiency of Hydrocarbon Fuels -- Chapter25: Information Technology for Security System Based on Cross Platform Software -- Chapter26: Active Remote Sensing of Chemical and Biological Agents: Detection, Remote Sensing, and Risk Analysis -- Index.
Biomedical and Life Sciences
text file PDF
Keywords: Nanoscale science; Nanoscience; Nanostructures; Nanotechnology; System safety; Quantum physics; Electronic circuits